Alternative dispute resolution and sustainability of economic development for the consumer’s benefit: an Islamic Moral Economy perspective - Ambaras Khan, Hanna; Foyasal Khan; Barua, Soura Jit (MMU Press, 2022)
Islamic Moral Economy (IME) rests on the idea of justice, goodness and fairness, and the social interest within the community. It provides a basic framework and moral-oriented principles to ensure the sustainability of economic development. In economics when contracts are formulated and signed, they are subjected to unexpected changes. Some issues may lead to disputes. The concept of Sulh (amicable settlement) can be used as an alternative dispute resolution (ADR) mechanism to solve these disputes. The scholars interpret such as mediation, arbitration, and conciliation. This paper aims to examine the potential of the applicability of mediation as a tool for dispute resolution in encouraging sustainability of economic development from an IME perspective. Based on a desk review of academic, peer-reviewed literature and reports, the particular focus of this study is on how mediation could assist the consumers of Islamic Banking and Finance in getting justice by applying dispute settlement methods between the parties. This paper suggested that the consumer obtains much benefit if the IME adopts ADR or mediation in resolving dispute and simultaneously maintains the sustainability of economic development.